Enigma variations: Unraveling interprofessional education in time and place. - Barr, Hugh (Journal of Interprofessional Care)
Designing the learning environment for the health care professionals of tomorrow is less than complete unless and until it includes interprofessional education (IPE). Progress depends on establishing a shared understanding of IPE between architects and teachers as the dialogue between them during the forum confirmed. My brief presentation provided no more than the catalyst. This paper goes further. It locates IPE within a coherent, consistent and pervasive rationale distilled over time from its roots in different countries and fields of practice, including the formulation of objectives, the adaptation of a repertoire of learning methods, the adoption of a definition and values and the framing of principle and competency-based outcomes, before alerting readers to some of the many complexities during the planning process.